2019
DOI: 10.3390/cells8111409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NV556, a Novel Cyclophilin Inhibitor, as a Potential Antifibrotic Compound for Liver Fibrosis

Abstract: Hepatic fibrosis can result as a pathological response to nonalcoholic steatohepatitis (NASH). Cirrhosis, the late stage of fibrosis, has been linked to poor survival and an increased risk of developing hepatocellular carcinoma, with limited treatment options available. Therefore, there is an unmet need for novel effective antifibrotic compounds. Cyclophilins are peptidyl-prolyl cis-trans isomerases that facilitate protein folding and conformational changes affecting the function of the targeted proteins. Due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
1
19
0
1
Order By: Relevance
“…Our recent work that show that both CRV431 and NV556 significantly decrease the development of liver fibrosis and hepatocellular carcinoma in non-alcoholic steatohepatitis mouse models [34][35][36], our present data suggest that the two entirely structurally different CypIs-CRV431 and NV556-derived from unrelated natural products, represent attractive partners to current DAA regimens for the treatment of hepatitis C and liver diseases.…”
Section: Plos Onesupporting
confidence: 68%
See 1 more Smart Citation
“…Our recent work that show that both CRV431 and NV556 significantly decrease the development of liver fibrosis and hepatocellular carcinoma in non-alcoholic steatohepatitis mouse models [34][35][36], our present data suggest that the two entirely structurally different CypIs-CRV431 and NV556-derived from unrelated natural products, represent attractive partners to current DAA regimens for the treatment of hepatitis C and liver diseases.…”
Section: Plos Onesupporting
confidence: 68%
“…CRV431 and NV556 exhibit apparent low toxicity in vivo . Indeed, we found that a daily oral administration of a high dose of CRV431 or NV556 (50 mg/kg) for extended periods of time (i.e., 14 to 30 weeks treatment) in mice did not induce unanticipated side effects [ 34 36 ]. This is in accordance with previous work conducted in humans that showed that a daily administration of the CypI alisporivir alone or in combination with ribavirin in HCV-infected patients in phase I, II, and III studies did not induce significant adverse effects [ 16 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…NV651 is a member of a family of the optimized cyclophilin inhibitors based on the sanglifehrin scaffold ( Figure 2 A). The platform also includes NV556, which we previously have evaluated for the treatment of fibrosis [ 32 ]. NV651 was selected based on the potency of the antiproliferative activity ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we characterized NV651, a novel SfA-based cyclophilin inhibitor demonstrated to be ten times more potent than SfA and a hundred times more potent than CsA, with no immunosuppressant activity [ 32 ]. Sorafenib is one of the main options for advanced HCC, prolonging the survival of patients up to three months [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly to this study, we recently demonstrated that CypI provide major beneficial therapeutic effects against the development of liver damage. We reported that CypI CRV431, Alisporivir or NV556 treatments alone significantly reduce both liver fibrosis and hepatocellular carcinoma in multiple nonalcoholic steatohepatitis (NASH) and nonalcoholic fatty liver disease (NAFLD) mouse models [40][41][42]. Our demonstration of the dual therapeutic effects of CypI that consist i) of suppressing efficiently HCV replication in an additive and synergistic effect when combined with NS5Ai, and ii) of preventing the deleterious development of liver fibrosis and liver cancer, reveals CypI as an interesting class of anti-HCV and anti-liver damage agents to be included into current DAA treatment to treat chronic hepatitis C and HCV-induced liver fibrosis and hepatocellular carcinoma.…”
Section: Plos Onementioning
confidence: 99%